Aspergillus niger boosted heat stress tolerance in sunflower and soybean via regulating their metabolic and antioxidant system. Issue 1 (1st January 2020) - Ismail,; Hamayun, Muhammad; Hussain, Anwar; Iqbal, Amjad; Khan, Sumera Afzal; Lee, In-Jung
ABSTRACT: Plants can be severely affected by heat stress due to rapid environmental changes. Use of endophytic fungi is a new tool to protect crops from the environmental stresses. Here we claim a potent endophyte isolated from Sonchus asper L. The aim was to explore the stress adaptive mechanism of sunflower and soybean mediated by Aspergillus niger (SonchL-7) under high temperature. Inoculation with A. niger boosted plant height, biomass and chlorophyl contents, while significantly curtailed the concentration of lipid peroxidation and reactive oxygen species (ROS) under thermal stress at 40°C. Moreover, the ROS-scavenging activities, like ascorbic acid oxidase (AAO), catalase (CAT), glutathione reductase (GR), superoxide dismutase (SOD) and peroxidase (POD) were augmented. Also, proline and phenolics were enhanced in the tested crops, while ABA concentration was significantly reduced. These positive results suggested that A. niger can be used as a heat-stress ameliorative tool for crops in the future.